2018
DOI: 10.1002/mc.22894
|View full text |Cite
|
Sign up to set email alerts
|

2′‐Hydroxyflavanone inhibits in vitro and in vivo growth of breast cancer cells by targeting RLIP76

Abstract: Consumption of citrus-fruits is associated with reduced incidence of breast cancer (BC), the most common cancer diagnosed in women across the globe. In this study, we investigated the anticancer potential of 2-Hydroxyflavanone (2HF) in BC. 2HF, a citrus-bioflavonoid, has demonstrated anticancer properties in various cancers, but its anticancer role in BC has not been well studied. We investigated the in vitro and in vivo growth inhibitory effects of 2HF in an array of BC lines and in xenograft mouse models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…We extensively studied and validated the phosphorothioated Rlip-specific antisense R508 in previous studies for its effects on Rlip depletion, tumor regression, apoptosis, cell cycling, and cell survival [ 7 , 27 , 50 , 51 ]. Previously, we demonstrated that R508-mediated Rlip depletion caused a concentration-dependent decrease in proliferation of the MCF7 cell line in culture [ 52 ]. Locked nucleic-acid-modified antisense oligonucleotides (LNAs) are third generation antisense molecules with improved pharmacological properties.…”
Section: Resultsmentioning
confidence: 99%
“…We extensively studied and validated the phosphorothioated Rlip-specific antisense R508 in previous studies for its effects on Rlip depletion, tumor regression, apoptosis, cell cycling, and cell survival [ 7 , 27 , 50 , 51 ]. Previously, we demonstrated that R508-mediated Rlip depletion caused a concentration-dependent decrease in proliferation of the MCF7 cell line in culture [ 52 ]. Locked nucleic-acid-modified antisense oligonucleotides (LNAs) are third generation antisense molecules with improved pharmacological properties.…”
Section: Resultsmentioning
confidence: 99%
“…In our recently published studies, we demonstrated the anticancer effects of 2HF in five BC cell lines, covering distinct receptor expression phenotypes: MDA‐MB231 (ER − /PR − /Her2 − ), SKBR3 (ER − /PR − /Her2 + ), MCF7 and T47D (ER + /PR + /Her2 − ), and MDA‐MB361 (ER + /PR − /Her2 + ) . We further demonstrated that the anticancer effect of 2HF was mediated through the inhibition/depletion of RLIP function/expression . In our previous studies on MCF7, MDA‐MB231, and SKBR3 cells, we determined that treating BC cells in vitro with a combination of 2HF and RLIP‐targeting agents reflected a similar response in vivo.…”
Section: Discussionmentioning
confidence: 51%
“…2HF is a natural phytochemical extracted from oranges that have inhibitory and chemopreventive effects in malignant cell lines . In our recently published studies, we demonstrated the anticancer effects of 2HF in five BC cell lines, covering distinct receptor expression phenotypes: MDA‐MB231 (ER − /PR − /Her2 − ), SKBR3 (ER − /PR − /Her2 + ), MCF7 and T47D (ER + /PR + /Her2 − ), and MDA‐MB361 (ER + /PR − /Her2 + ) . We further demonstrated that the anticancer effect of 2HF was mediated through the inhibition/depletion of RLIP function/expression .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations